2007
DOI: 10.1073/pnas.0706295104
|View full text |Cite
|
Sign up to set email alerts
|

A herpesvirus ubiquitin-specific protease is critical for efficient T cell lymphoma formation

Abstract: The herpesvirus ubiquitin-specific protease (USP) family, whose founding member was discovered as a protease domain embedded in the large tegument protein of herpes simplex virus 1 (HSV-1), is conserved across all members of the Herpesviridae. Whether this conservation is indicative of an essential function of the enzyme in vivo has not yet been established. As reported here, USP activity is conserved in Marek's disease virus (MDV), a tumorigenic alphaherpesvirus. A single amino acid substitution that abolishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 37 publications
4
91
0
Order By: Relevance
“…These observations notwithstanding, to date there have been few clues as to the role of the USP activity, and while it can have a dramatic effect in certain circumstances (21,27), no rationale for the high conservation of the USP across viruses with diverse pathways of infection and pathogenesis. Furthermore, apart from cleavage of polyubiquitin chains in vitro, there has been little evidence that the USP can deubiquitinate a substrate and influence its degradation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…These observations notwithstanding, to date there have been few clues as to the role of the USP activity, and while it can have a dramatic effect in certain circumstances (21,27), no rationale for the high conservation of the USP across viruses with diverse pathways of infection and pathogenesis. Furthermore, apart from cleavage of polyubiquitin chains in vitro, there has been little evidence that the USP can deubiquitinate a substrate and influence its degradation.…”
Section: Discussionmentioning
confidence: 98%
“…In studies of a similar PRV mutant containing a C26A mutation, virus yields in culture were delayed and lower (10-to 20-fold), and a very significant defect was observed in animal models of neuroinvasion from peripheral tissues (27). In the MDV VP1-2 homologue, it was reported that a single substitution in the active site of the enzyme abolished its ubiquitin cleavage activity in vitro, and while the corresponding mutation in the context of a recombinant virus had a modest though detectable effect on replication (4-fold lower yields and up to 50% reduction ion plaque size), it had a profound effect on in vivo pathogenesis, with a 1,000-to 10,000-fold reduction in viremic levels and a drastic reduction in T cell lymphomas in infected chickens (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Samples of 20 g total RNA were resolved in a 15% polyacrylamide-urea gel and blotted onto a GeneScreen Plus membrane (Perkin-Elmer). DNA oligonucleotides with the exact complementary sequence to selected miRNAs were end labeled with [␥- 32 P]ATP by use of T4 polynucleotide kinase (New England Biolabs, Hertfordshire, United Kingdom) to generate high-specific-activity probes. Hybridization, washing, and autoradiography were carried out as previously described (36,53).…”
Section: Methodsmentioning
confidence: 99%
“…Some of the functions of Meq associated with oncogenic properties, such as its interaction with CtBP, parallel those of other viral oncogenic sequences, such as adenovirus E1A and Epstein-Barr virus (EBV) nuclear antigens EBNA3A and -3C (6), highlighting the convergent evolution of oncogenic pathways in these viruses. Recent studies have also identified the role of other genes, such as the pp38 (23), viral interleukin-8 (vIL-8) (49), ICP4 (15,38), R-LORF4 (33), UL36 (32), and MDV-encoded telomerase RNA (22,63) genes, in pathogenesis.…”
mentioning
confidence: 99%